The effect of CoPt-coated reduced-graphene oxide nanosheets upon the Smectic-A to Smectic-C* phase transition of a chiral liquid crystal. Issue 6 (2nd May 2020) - Lavrič, Marta; Cordoyiannis, George; Tzitzios, Vasileios; Kralj, Samo; Nounesis, George; Lelidis, Ioannis; Amenitsch, Heinz; Kutnjak, Zdravko
ABSTRACT: We report on high-resolution calorimetry and small-angle X-ray scattering measurements along the Smectic-A to chiral Smectic-C* phase transition of the liquid crystal 4-(2-methyl butyl) phenyl 4-n-octylbiphenyl-4-carboxylate with dispersed, CoPt nanoparticle-coated reduced-graphene oxide nanosheets. The temperature dependence of heat capacity and smectic layer spacing are obtained in the vicinity of Smectic-A to chiral Smectic-C* phase transition. Though no remarkable pretransitional effects are present, the critical fits show a crossover from mean-field near a tricritical point to classical mean-field compared to pure liquid crystal. The X-ray data yield a dilation of smectic layer thickness, indicating the assembly of graphene oxide nanosheets between the smectic layers. GRAPHICAL ABSTRACT: